THE ANALYSIS OF FACTORS AFFECTING EMPLOYEE RETENTION AT PT. HASJRAT ABADI MANADO - Walangitan, Briando N.V.; Pangemanan, Sifrid S.; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Employee is a valuable asset that needs to be well-organized for acquiring a maximum organization performance. In other words, by using appropriate employee retention program would be very critical for creating sustainability of any organization. Therefore, this research study aims to investigating factors that affecting employee retention at PT. Hasjrat Abadi Manado such as: stress management, employee personal value match with job, employee empowerment and involvement, positive work experiences, compensation, training, supervisor support, mentoring, reward and recognition, fair performance appraisal with feedback, work-life balance, career development, organizational justice, organizational prestige, organizational commitment, location, job security, sense of belonging, andÂ  interpersonal relationship. Specifically, the study sought to determine the association of interrelated employee retention variables by adopted the analysis of factors as a main research method. A sample size of 50 respondents from 105 permanent employees was used for study. Data was collected primarily through personal interview and self-administered survey and interpreted by using Statistical Program for Social Science. From the overall results, training has the most significant influence, and it followed by job security, mentoring, and employee empowerment and involvement. however, not all of factors evaluated that have strong influence to employee retention approach at PT. Hasjrat Abadi Manado. Keywords: employee retention, performance